2003
DOI: 10.1007/s00134-003-1937-2
|View full text |Cite
|
Sign up to set email alerts
|

A prospective randomized trial of enteral glutamine in critical illness

Abstract: This clinical trial did not support the use of enteral glutamine supplements in similar cohorts of critically ill patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
1
10

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(60 citation statements)
references
References 35 publications
0
49
1
10
Order By: Relevance
“…Lower-dose glutamine Brantley & Pierce (12) Déchelotte et al (15) Fuentes-Orozco et al (18) Griffiths et al (21) Hall et al (22) Jones et al (25) Kumar et al (27) Luo et al (28) Ockenga et al (33) Perez-Barcena et al (36) Sahin et al (38) Tjäder et al (41) Wischmeyer et al (42) Subtotal ( (P=0·11) 14 1 2 2 11 4 0 10 47 32 22 21 72 41 10 59 304 9 6 5 10 21 3 2 4 37 31 22 24 72 39 10 64 299 1·32 0·13 0·34 0·15 0·44 1·30 0·16 3·06 0·66 0·50, 3·51 0·02, 1·19 0·06, 1·98 0·03, 0·78 0·19, 0·99 0·27, 6·21 0·01, 3·85 0·90, Categorisation into critical illness or surgical trials was difficult. Trials in which participants had pancreatitis or surgery followed by complications, e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lower-dose glutamine Brantley & Pierce (12) Déchelotte et al (15) Fuentes-Orozco et al (18) Griffiths et al (21) Hall et al (22) Jones et al (25) Kumar et al (27) Luo et al (28) Ockenga et al (33) Perez-Barcena et al (36) Sahin et al (38) Tjäder et al (41) Wischmeyer et al (42) Subtotal ( (P=0·11) 14 1 2 2 11 4 0 10 47 32 22 21 72 41 10 59 304 9 6 5 10 21 3 2 4 37 31 22 24 72 39 10 64 299 1·32 0·13 0·34 0·15 0·44 1·30 0·16 3·06 0·66 0·50, 3·51 0·02, 1·19 0·06, 1·98 0·03, 0·78 0·19, 0·99 0·27, 6·21 0·01, 3·85 0·90, Categorisation into critical illness or surgical trials was difficult. Trials in which participants had pancreatitis or surgery followed by complications, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Critical illness EN Conejero et al (13) Garrel et al (19) Hall et al (22) Houdijk et al (23) Kumar et al (27) Schulman et al (39) Subtotal (95 % CI)…”
Section: Methodsmentioning
confidence: 99%
“…A number of laboratory studies have confirmed the gut-protective effects of enteral glutamine administered to the postischemic gut (26,38). Additionally, clinical studies have demonstrated that enteral glutamine administered to trauma, burn, and critically ill patients decreases morbidity in most but not all studies (3,17,19,23,42,64). We have shown that the early use of glutamine during active shock resuscitation is safe (37).…”
Section: Discussionmentioning
confidence: 72%
“…[33] Researchers believe that Gln is potentially 'life-saving' in critical illness, particularly when it is administered at a parenteral dose of over 0.3 g/kg per day. [34][35][36] In conclusion, parenteral Gln administration can up-regulate serum HSP-70 concentration, decrease the levels of AST, ALT,TbiL, TNF-α, and IL-6, shorten the length of mechanical ventilation and ICU stay, and improve the ratio of CD4/CD8 in critical patients with acute liver injury. The correlation between Gln and HSP70 found in this study suggests that early parenteral glutamine administration could improve outcomes of critical patients with acute liver injury by increasing the expression of heat shock protein..…”
Section: Discussionmentioning
confidence: 87%